Serum lactate dehydrogenase levels and glycolysis significantly correlate with tumor VEGFA and VEGFR expression in metastatic CRC patients. (December 2007) - Azuma, Mizutomo; Shi, Michael; Danenberg, Kathleen D; Gardner, Humphrey; Barrett, Carl; Jacques, Christian J; Sherod, Andrew; Iqbal, Syma; El-Khoueiry, Anthony; Yang, Dongyun; Zhang, Wu; Danenberg, Peter V; et al.
Objectives: In an attempt to elucidate the relationship between biomarkers of tumor hypoxia, glycolysis and angiogenesis, we tested the hypothesis that intratumoral gene expression of the hypoxia response (hypoxia inducible factor [ HIF1αα and 2αα ]), glycolysis (lactate dehydrogenase A [ LDHA ]), glucose metabolism (glucose transporter-1 [ Glut-1 ]) and genes involved in angiogenesis (i.e., VEGFA, VEGFR1––3, and neuropilin [ NRP ] 1 ) are upregulated in metastatic colorectal cancer (mCRC) patients with high serum lactate dehydrogenase (LDH).Patients and methods: 78 formalin-fixed, paraffin-embedded (FFPE) tumor samples were collected from 36 patients with mCRC. Tumor gene expression was correlated with serum LDH levels from the same group of patients. FFPE tissues were dissected using laser-captured microdissection and analyzed for gene expression using a quantitative real-time RT-PCR method.Results: Intratumoral gene expression of VEGFA and VEGFR1 showed a statistically significant correlation with serum LDH levels (p = 0.006, r = 0.45 and p = 0.004, r = 0.50, respectively). Intratumoral expression of LDHA gene showed a significant correlation with Glut-1, VEGF, HIF1αα, HIF2αα and VEGFR1 (p = 0.007, r = 0.44; p < 0.001, r = 0.57; p = 0.013, r = 0.41; p = 0.044, r = 0.34; p = 0.026, r = 0.40). Serum LDH levels also correlated with microvessel density analyzed by immunohistochemical analysis.Conclusion: The results demonstrated a significant correlation between the intratumoral gene expression of LDHA, HIF1αα, HIF2αα, Glut-1, NRP1, VEGFA and VEGFR1 . Patients with high serum LDH have increased intratumoral gene expression of VEGFA and VEGFR1 . The results also support the hypothesis that serum LDH levels may serve as a surrogate marker for activation of the HIF-related genes in the tumor.